Interventional Oncology in Immuno-Oncology Part 2: Transcatheter Therapies - Dendy Case, Meaghan; Slovak, Ryan; Raja, Junaid; Kim, Hyun S. (Digestive Disease Interventions, 2019)
The use of transcatheter embolization in its various forms in interventional oncology has altered the treatment paradigms for multiple types of cancer. Though direct investigation of the immunologic effects of transcatheter treatments has been limited, research on radiation therapy can be extrapolated to better understand the potential effects of radioembolization and studies on the immune response to chemotherapy can potentially explain the immune response to hepatic artery infusion and chemoembolization. Utilization of newer systemic immunotherapies in combination with various transcatheter therapies also presents the potential for improving outcomes for multiple malignancies. This review will discuss the role of transcatheter therapies in stimulating an immune response as well as the potential these techniques have to enhance the effects of systemic immunotherapy.
Keywords: transcatheter; immuno-oncology; abscopal